Diabetology & Metabolic Syndrome - Vencio, Sergio
Diabetology & Metabolic Syndrome publishes articles on all aspects of the pathophysiology of diabetes and metabolic syndrome. By publishing original material exploring any area of laboratory, animal or clinical research into diabetes and metabolic syndrome, the journal offers a highly visible forum for new insights and discussions into the issues of importance to the relevant community. The journal aims to help health care providers improve the management of people afflicted by these syndromes by increasing knowledge and stimulating research in the field. Diabetology & Metabolic Syndrome reports on basic research and clinical studies in the areas of genetics, pathophysiology, immunology, epidemiology, clinical management, therapeutic strategies, education, nutrition and psychosocial research relevant for the study of diabetes and metabolic syndrome.